Drivers of winter indoor temperatures in Swedish dwellings: Investigating the tails of the distribution. (September 2021) - Teli, Despoina; Psomas, Theofanis; Langer, Sarka; Trüschel, Anders; Dalenbäck, Jan-Olof
Abstract: Residential indoor climate is a key factor for occupant comfort, health and wellbeing, while also affecting the buildings' energy demand. A strong focus has been traditionally placed on low winter indoor temperatures in dwellings due to their considerable health impacts. However, there is a trend towards high and stable indoor temperatures, which also have significant implications. This paper investigates the drivers of winter indoor temperatures by analysing the following three metrics of measured temperatures in a sample of 1039 Swedish dwellings: a) level, through the sample dwellings' standardised indoor temperatures at 5 °C outdoor temperature, b) daily variation, through the standard deviation of the indoor temperature and c) shape, using daily indoor temperature profiles derived from cluster analysis. The study explores the association of these metrics to building-, dwelling- and occupant-related parameters. The analysis shows that 80% of the standardised indoor temperatures were above 21 °C, with one third of the latter being above 23 °C, while 82% of dwellings had constant temperatures throughout the day. High winter indoor temperatures were more evident in middle-placed apartments in multi-family buildings connected to district heating and in better insulated single-family houses. High temperatures were also associated with experiencing draft from windows, too warm conditions in winter and difficulty to control the indoor temperature, but not with the overall thermal comfort assessment which was very positive in both the high and low temperature tails. Long-term adaptation effects, established norms and comfort expectations are discussed as important confounding factors in the development of residential indoor temperatures. Highlights: Winter indoor temperatures of 1039 Swedish dwellings were analysed. One quarter of the dwellings' standardised temperatures were above 23 °C. High winter indoor temperatures occur mostly in district-heated, middle-placed apartments. Evidence of rebound effects in better insulated single-family houses. Effects of thermal adaptation, established norms and expectations are discussed.